Synthesis of a series of quinoxaline derivatives and their antibacterial effectiveness against pathogenic bacteria - Khatoon, Hena; Abdul Malek, Emilia; Faudzi, Siti Munirah; Rukayadi, Yaya (John Wiley and Sons Inc, 2024)
The pharmacological importance of quinoxaline derivatives in antibacterial research is well recognized. This study focuses on the synthesis of new 2,3-dichloroquinoxaline derivatives containing thioether/ether groups to explore their potential as potent antibacterial agents against various pathogenic bacteria. Most of the compounds exhibited significant antibacterial properties comparable to the standard drug chlorhexidine (CHX). The derivatives of 2-chloro-3-(arylthiol)quinoxaline demonstrated efficacy against Escherichia coli with minimum inhibitory concentrations (MIC) of 2.5 mg/mL and minimum bactericidal concentrations (MBC) of 2.5 to 5.0 mg/mL. These derivatives also showed similar sensitivity to Bacillus pumilus. In addition, molecular docking simulations were performed to investigate the interaction between the synthesized compounds and the DNA gyrase protein (PDB ID: 1KZN), a target for antibiotics. Among the synthesized compounds, 2,3-bis(3-nitrophenoxy)quinoxaline exhibited the most favourable docking score of −8.36 kcal/mol, with a binding affinity comparable to that of the reference ligand clorobiocin (−9.3 kcal/mol).